(untitled) (Delta Medical College Journal, 2016)
Background: Hazardous use of alcohol is a public health problem which accounts for 4.0% of global burden of disease. There are very few studies about alcohol consumption trend among tribal in Bangladesh. We investigated the pattern and trend with reasons for alcohol use in Hill Tract dwellers with the aim to increase the awareness of this problem. Objective: To identify the pattern of alcohol use and its effect among the tribal so that effective measures can be taken to eliminate the social evil. Materials and method: This cross-sectional study was conducted among tribal community of Chittagong Hill Tracts, Rangamati district, Bangladesh between June 2014 to February 2015. Out of 846 people coming in Naniarchor and Langadu upazila health complexes 716 (84.6%) constituted the study group. The CAGE test was used as a screening test in determining alcohol dependence. Results: The prevalence of alcohol consumption among tribal is 48.9%. Rural areas (65%) are the most vulnerable area. Home-made alcohol (61%) was the most patronized alcoholic beverage. Most of the cases (82%) started alcohol before 30 years of age and 46% participants took alcohol daily. To get pleasure is the commonest factor for taking alcohol (57%). Physical and mental degenerations were found in most of the alcoholic cases (88%). Conclusion: The results of the present study are likely to increase the awareness of the problem in hill areas and help the concerned authorities to shape the requisite alcohol control policies in these regions. Delta Med Col J. Jan 2016 4(1): 4-8